EFFICACY OF PATHOGENETIC THERAPY FOR ATOPIC DERMATITIS IN INFANTS - T.G. Malanicheva; L.A. Khaertdinova (Union of pediatricians of Russia, 2010)
The article looks at the issue of atopic dermatitis as a manifestation of atopic march in infants. Authors provide results of their own observations in the use of modern topical steroid - mometasone furoate - in the integrated therapy. This glucocorticosteroid does not contain fluorine and has predominantly non-genomic mechanism. The results of the study evidenced a high efficacy and good tolerance to this topical steroid. Key words: atopic dermatitis, children, momethasone furoate. (Pediatric Pharmacology. - 2010; 7(2):87-90)